1990
DOI: 10.1073/pnas.87.21.8301
|View full text |Cite
|
Sign up to set email alerts
|

Downstream secondary structure facilitates recognition of initiator codons by eukaryotic ribosomes.

Abstract: Recognition of an AUG initiator codon in a suboptimal context improves when a modest amount of secondary structure is introduced near the beinning of the protein-coding sequence. This facilitating effect depends on the position of the downstream stem-loop (hairpin) structure. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
405
1
4

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 505 publications
(439 citation statements)
references
References 41 publications
(46 reference statements)
20
405
1
4
Order By: Relevance
“…Wang ever, because DB is located downstream from stemloop I, the latter may be involved with binding to the ribosome complex, but may not be a part of the specific geometric arrangement deterring ribosomal movement+ The presence of a pseudoknot, stem-loops II, III, and IVA complex structure further downstream from the DB could serve the function of retarding the downstream movement of ribosome prior to a sound and error-proof recognition of the initiation codon (Kozak, 1990)+ The presence of a potential IRES downstream from the initiation codon has been also observed among some of the other viral transcripts+ For hepatitis A virus, inclusion of more than 114 nt of its 59 capsid-coding transcript enhances the translation by three-to fourfold (Graff & Ehrenfeld, 1998)+ Inclusion of the first 266 nt of the 59 capsid-coding sequence of the Sinbdis viral transcript enhances translation by 10-fold (Frolov & Schlesinger, 1996)+ Our current identification of putative downstream IRES in GLV mRNA may yet carry an additional biological significance beyond an interesting phenomenon among the viruses+ The dependence of GLV on downstream IRES for translation could also reflect one of the uniquely primitive features of the translation machinery and mechanisms operating in its host, Giardia+ The cellular mRNAs in this primitive protozoan are mostly uncapped (Yu et al+, 1998) and have very short 59 UTR in the range of 1 to 6 nt (Adam, 1991)+ In the absence of a cap and a substantial 59 UTR, how mRNA molecules can recruit the 40S ribosome subunit to the precise decoding region to initiate translation has not been clearly understood+ The GLV transcript is translated by the same machinery as the cellular mRNA of Giardia, and translation of the viral mRNA is known to exert no inhibitory effect on translation of cellular mRNA (Wang & Wang, 1986)+ Insights obtained from localizing the IRES in the downstream region and analyzing the structure-function relationship of the IRES in GLV mRNA may shed some light on whether the cellular mRNA in Giardia could also depend on similar elements present downstream of the initiation codon for translation initiation+ Thus, translation of GLV transcript may serve as a model system for understanding the translational initiation mechanisms in this most primitive and one of the earliest diverging and living eukaryotes known to man+…”
Section: Discussionmentioning
confidence: 99%
“…Wang ever, because DB is located downstream from stemloop I, the latter may be involved with binding to the ribosome complex, but may not be a part of the specific geometric arrangement deterring ribosomal movement+ The presence of a pseudoknot, stem-loops II, III, and IVA complex structure further downstream from the DB could serve the function of retarding the downstream movement of ribosome prior to a sound and error-proof recognition of the initiation codon (Kozak, 1990)+ The presence of a potential IRES downstream from the initiation codon has been also observed among some of the other viral transcripts+ For hepatitis A virus, inclusion of more than 114 nt of its 59 capsid-coding transcript enhances the translation by three-to fourfold (Graff & Ehrenfeld, 1998)+ Inclusion of the first 266 nt of the 59 capsid-coding sequence of the Sinbdis viral transcript enhances translation by 10-fold (Frolov & Schlesinger, 1996)+ Our current identification of putative downstream IRES in GLV mRNA may yet carry an additional biological significance beyond an interesting phenomenon among the viruses+ The dependence of GLV on downstream IRES for translation could also reflect one of the uniquely primitive features of the translation machinery and mechanisms operating in its host, Giardia+ The cellular mRNAs in this primitive protozoan are mostly uncapped (Yu et al+, 1998) and have very short 59 UTR in the range of 1 to 6 nt (Adam, 1991)+ In the absence of a cap and a substantial 59 UTR, how mRNA molecules can recruit the 40S ribosome subunit to the precise decoding region to initiate translation has not been clearly understood+ The GLV transcript is translated by the same machinery as the cellular mRNA of Giardia, and translation of the viral mRNA is known to exert no inhibitory effect on translation of cellular mRNA (Wang & Wang, 1986)+ Insights obtained from localizing the IRES in the downstream region and analyzing the structure-function relationship of the IRES in GLV mRNA may shed some light on whether the cellular mRNA in Giardia could also depend on similar elements present downstream of the initiation codon for translation initiation+ Thus, translation of GLV transcript may serve as a model system for understanding the translational initiation mechanisms in this most primitive and one of the earliest diverging and living eukaryotes known to man+…”
Section: Discussionmentioning
confidence: 99%
“…For example, a stable secondary structure located 13-17 nucleotides downstream of the start codon could delay 40S movement in the proper position and facilitate the recognition of TIS in a weak context, but the frequency of this signal in eukaryotic transcriptome was not analyzed. (8,9) The results of some computational evaluations showed the potential importance of a nucleotide in position þ5 and a second codon of the CDS as well as some other mRNA regions. (10)(11)(12)(13) The initiation of translation may also sometimes occur at non-AUG codons.…”
Section: Eukaryotic Mrnas and Translation Initiation Mechanismsmentioning
confidence: 99%
“…6A), that could facilitate its recognition. It has been shown that recognition by mammalian ribosomes of an AUG codon in a suboptimal context, as well as that of non-AUG codons in general, is enhanced by the presence of a downstream stem-loop (hairpin) structure (29). In fact, this appears to be a common feature for many of the mRNAs whose translation has been shown to initiate at non-AUG codons (30).…”
Section: Discussionmentioning
confidence: 99%